GLUTATHIONE S TRANSFERASE PROTEIN, NUCLEIC ACID, CHROMATIN, CELL NUCLEI AND STRUCTURAL VARIATION ANALYSIS OF ERYTHROCYTE, BONE MARROW CELL AND HEPATOCYTES OF RATS UNDER THE INFLUENCE OF ACRYLAMIDE - S. N. VEENAPANI; M. MEENA BAI; A. UMA; K. VENKATASUBBAIAH; K. J. RAO; K. THYAGARAJU (The Bioscan, 2010)
Glutathione s transferases (GSTs; EC, 2.5.1.18), a family of multifunctional and versatile proteins, are found almost in all organisms that are living in aerobic environment. The present study was conducted on rat GSTs using dot blot, ELISA, genomic DNA analysis, micronuclei comet assay and histopathological studies in control and acrylamide treated rat liver tissues. In dot blot analysis studies rat serum GSTs showed high immunoprecipitation and ELISA analysis results showed higher O.D values at 12mg and 36mg of acrylamide treatment than control values. In isolated genomic DNA, degradation was observed in all treated tissues indicating damage to hepatocytes of rats. The positive genotoxic effects were also observed by the formation of micronuclei. In these studies more of micronuclei were observed at 36mg AC. In comet assay the diffusion of nuclear head formation was started from 24mg of dosage and a full comet characteristic of necrosis was appeared at 36mg of dosage. To confirm the production of more of GST proteins, damage to DNA, chromatin and nuclei the histological changes were conducted. These studies on rat liver tissues have revealed a pathological change in hepatocyte on exposure to Acrylamide with different doses at different time intervals. Therefore our experimental analysis has revealed that the GSTs can be used as biomarkers for the detection of cancers and chemical toxicity which are caused by acrylamide and other drugs/chemicals.